(untitled) - Nguyễn, Mân (Thành phố Hồ Chí Minh, 1984)
Cuốn sách hướng dẫn trồng các loại rau cải bắp, bông cải, đậu cove, dưa leo, cà chua,...
Keywords: Vegetables,Hướng dẫn trồng rau đậu,Tomatoes; Diseases and pests,Manual,Diseases and pests